EMERGENCE OF TECHNOLOGICAL INNOVATIONS IN DIGITAL HOSPITALITY ‒ LITERATURE REVIEW - Zrnić, Miloš; Božić, Aleksandar (The Business of Tourism, 2024)
The hospitality industry is undergoing a significant transformation driven by technological advancements, leading to the emergence of digital hospitality. This paper addresses the drivers, challenges and opportunities associated with the digitization of hospitality services, offering valuable insights for industry stakeholders. Through an exploration of case studies, industry trends and theoretical frameworks, this paper reveals the transformative power of digital hospitality and its implications for the future of the industry. The findings reveal that the adoption of technical innovations such as virtual reality, contactless technology and artificial intelligence are reshaping the way hospitality services are delivered and experienced. Industry leaders are using these technologies to improve customer experience, optimize operations and drive sustainability initiatives. Moreover, the paper highlights the importance of tailored strategies and interventions aimed at reducing waste, improving efficiency and meeting the growing demands of consumers in the digital era. Also, the paper emphasizes the need for companies in the hospitality sector to embrace digitization and adapt to the changing landscape. By embracing technological advances and implementing innovative solutions, organizations can position themselves for success in a digitally driven world, ultimately increasing competitiveness and customer satisfaction in the evolving hospitality industry.